FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN EMISI KARBON DAN REAKSI SAHAM PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Rezka Krisna Wardhani; Warsito Kawedar (Diponegoro Journal of Accounting, 2019)
The purpose of this study was to examine the effect of liquidity, financial performance, and the reputation of public accounting firms on disclosure of carbon emissions and the reaction of shares in manufacturing companies in Indonesia. The population in this study consisted of manufacturing companies in the Indonesia Stock Exchange for the period 2013 - 2017 that publish annual reports and disclose carbon emissions. Sampling is done using the purposive sampling method. The total sample of this study was 78 companies. This study uses multiple regression analysis to test hypotheses. The results of this study indicate that all independent variables such as liquidity, financial performance, and the reputation of public accounting firms have a positive influence on disclosure of carbon emissions. However, in reaction to stocks only liquidity has a positive effect.